A reasonable inlet boundary for wind simulation based on a trivariate joint distribution model. Issue 233 (February 2023) - Xing, Longfei; Zhang, Jinxiang; Zhang, Mingjin; Li, Yongle; Zhang, Shuai; Yan, Tingyuan
Abstract: In mountainous regions, the height of the atmospheric boundary layer (ABL) plays a crucial role in accurately simulating the wind field. In order to uncover the correlation between the complex terrain and the ABL height, the required samples were obtained via the WRF experiment taking a mountainous region in Southwestern China as the research object. The Pair-Copula decomposition method was then employed to create a trivariate joint distribution model of the atmospheric boundary layer elevation, the terrain elevation, and the surface relief degree based on the samples. The trivariate joint distribution model shows that the ABL field fluctuates more in the regions with higher surface undulation and less in the regions with lower surface undulation. Furthermore, the model can be used to evaluate the probability distribution of the ABL height over the complex terrain where a projected bridge will locate, thereby providing a more reasonable inlet boundary to simulate the wind environment surrounding the bridge. The method presented here for correlating the ABL height with terrain is universal and can be extended to wind field simulation in many regions. Highlights: A method for describing the correlation between ABL height and complex terrain is proposed. The joint probability distribution of ABL height and complex terrain is constructed. Based on the joint distribution model, an analysis of ABL height over the complex terrain can be carried out.